The Parastate in Colombia: Political Violence and the Restructuring of Barrancabermeja - Gill, Lesley (Anthropologica, 2022)
This article examines how terror and fear hastened the neoliberal restructuring of Barrancabermeja and the creation of a violent surrogate state. It argues that neoliberal reforms arose in the context of a severe social crisis. Massive violence and disorder ruptured social solidarities and facilitated the incorporation of some working people into exploitative forms of labour regulation, rent extraction and political subjugation that deepened neoliberalism and undergirded the creation of a public order in which the private power of paramilitarism merged with the state.